Grubbing out the Führerbunker: Ruination, demolition and Berlin’s difficult subterranean heritage - Bennett, Luke. Autor (IGiPZ PAN, 2019)
This article presents a case study examining the slow-death of the Berlin Führerbunker since 1945. Its seventy year longitudinal perspective shows how processes of ruination, demolition and urban renewal in central Berlin have been affected by materially and politically awkward relict Nazi subterranean structures. Despite now being a buried pile of rubble, the Führerbunker’s continued resonance is shown to be the product of a heterogeneous range of influences, spanning wartime concrete bunkers’ formidable material resistance, their affective affordances and evolving cultural attitudes towards ruins, demolition, memory, memorialisation, tourism and real estate in the German capital.
24 cm
Keywords: ruin; demolition; bunkers; subterranean; Berlin; nasizm; heritage; materiality